THE USE OF MIND MAPPING TECHNIQUE TO TEACH WRITING OF NARRATIVE TEXT TO THE ELEVENTH GRADE (RETAIN, 2014)
THE USE OF MIND MAPPING TECHNIQUE TO TEACH WRITING OF NARRATIVE TEXT TO THE ELEVENTH GRADE Enty Novilasari English Departement, Languages and Arts Faculty, State University of Surabaya ndtired@gmail.com Himmawan Adi Nugroho, S.Pd., M.Pd English Departement, Languages and Arts Faculty, State University of Surabaya himmawan_95@yahoo.co.id Abstrak Bahasa Inggris adalah salah satu bahasa penting di dunia ini . Ini adalah salah satu dari banyak alasan mengapa kita harus belajar bahasa Inggris dalam kehidupan sehari-hari kita adalah untuk mendapatkan pekerjaan yang baik karena banyak perusahaan raksasa berasal dari negara-negara asing . Ini berarti salah satu persyaratan untuk mendapatkan pekerjaan yang baik adalah menguasai bahasa Inggris yang dianggap sebagai bahasa internasional . Ada empat dasar-dasar keterampilan bagi kita untuk menguasai bahasa Inggris. Salah satu keterampilan penting adalah menulis. Menulis dianggap sebagai keterampilan yang sulit , terutama bagi siswa yang belajar bahasa Inggris sebagai bahasa kedua. Hal ini didukung oleh Richard dan Renandya ( 2002) yang menyatakan bahwa menulis adalah keterampilan yang paling sulit bagi pembelajar bahasa kedua. Oleh karena itu guru harus memberikan teknik alternatif untuk membantu siswa dalam menulis. Karena kasus itu, teknik pemetaan pikiran dapat menjadi alat untuk membantu siswa mengatur ide-ide sebelum mereka melakukan proses penulisan mereka. Mind Mapping adalah sebuah organizer yang merupakan representasi visual dengan tema sentral dikelilingi oleh cabang , tema , gambar , gambar , pikiran , pola , dan ide-ide yang diambil dari informasi yang diberikan selama kuliah kelas ( Trevino , 2005). Dalam penulisan mengajar ada empat langkah yang digunakan dalam pelaksanaan pemetaan pikiran : penjelasan guru , memberikan topik ; membuat pemetaan pikiran ; dan proses menulis . Dan langkah-langkah yang diterapkan dalam kegiatan siswa selama proses belajar-mengajar . Penelitian ini dilakukan di MAN 2 Gresik . Subyek penelitian ini adalah 25 siswa kelas XI - A1 . Penelitian ini merupakan penelitian deskriptif kualitatif yang menggambarkan pelaksanaan pemetaan pikiran untuk mengajar menulis teks narasi Berdasarkan hasil penelitian ini , penggunaan teknik pemetaan pikiran adalah sebagai bantuan untuk mengatur ide-ide siswa sebelum melakukan proses penulisan . Guru menjelaskan bagaimana menggunakan pemetaan pikiran sebelum kegiatan . Para siswa menggunakannya dalam kelompok dan secara individu sebelum proses penulisan mereka . Guru telah mengingatkan siswa struktur generik dan fitur bahasa teks narasi tetapi tampak beberapa siswa lupa itu . Kemudian , ia mencoba menjelaskan lagi . Selama proses belajar-mengajar , para siswa tampak aktif dan antusias . Berdasarkan karya siswa , setelah peneliti menganalisis menggunakan Jacob Profil komposisi ESL . Hal ini diketahui bahwa sebagian besar siswa dalam kriteria baik . Ini berarti bahwa mereka dapat membuat se narasi dengan baik . Dengan demikian dapat disimpulkan bahwa pemetaan pikiran adalah efektif sebagai teknik untuk membantu siswa mengatur dan menghasilkan ide-ide mereka . Para guru masih harus memperhatikan kemampuan menulis siswa selama proses belajar-mengajar . Kata kunci : Menulis , Mind Mapping dan teks Narrative Abstract English is one of the important languages in this world. It is one of many reasons why we must learn English in our daily life is to get a good job because many giant companies come from foreign countries. It means one of requirements to get a good job is mastering English which is considered as an international language. There is four basics skills for us to master an English. One of the important skills is writing. Writing is considered as a difficult skill, especially for students who learn English as a second language. It is supported by Richard and Renandya (2002) who stated that writing is the most difficult skill for second language learners. Therefore the teacher should give an alternative technique to help students in their writing.. Due to that case, mind mapping technique can be a tool to help students organize the ideas before they do their writing process. Mind Mapping is an organizer that is a visual representation with a central theme surrounded by branches, themes, images, pictures, thoughts, patterns, and ideas taken from information given during a class lecture (Trevino, 2005). In teaching writing there are four steps those are used in the implementation of mind mapping: teachers’ explanation, giving the topic; making a mind mapping; and writing process. And those steps are implemented in the students’ activities during the teaching-learning process. This research was conducted in MAN 2 Gresik. The subjects of this research were 25 students of class XI-A1. It was a descriptive qualitative research which described the implementation of mind mapping to teach writing of narrative text Based on the result of this research, the use of mind mapping technique is as a help to organize the students’ ideas before doing the writing process. The teacher explained how to use mind mapping before the activity. The students using it in group and individually before their writing process. The teacher had reminded the students the generic structures and language feature of narrative text but seemed some of the students forgot it. Then, he tried to explain it again. During the teaching-learning process, the students looked active and enthusiastic. Based on the students’ work, after the researcher analyzes using Jacob composition ESL Profile. It is known that most of students are in good criteria. It means that they can compose se narrative well. It can be concluded that a mind mapping was effective as a technique to help students organize and generate their ideas. The teachers still have to pay attention in students’ writing ability during teaching-learning process. Keywords: Writing, Mind Mapping and Narrative text INTRODUCTION As we all know, in globalization era today, English is one of the important languages in this world. It can be seen from the great enthusiasm of Indonesian in learning English as a second language. One of the reasons why we must learn English in our daily life is to get a good job. Many giant companies come from foreign countries. It means one of requirements to get a good job is mastering English which is considered as an international language. Based on the explanation above, Indonesian government through the national education has determined that English must be taught from the elementary schools until senior high schools. By mastering English, it is easier for us to make a good relationship with other countries. In education context, English has function as a means to communicate in the daily communication, to get knowledge, to make interpersonal communication, to share information and to enjoy language lesson in English culture (Depdikbud, 2006). In Indonesia, English is taught in junior high school and senior high school, even in elementary school that is why studying English is not a new thing for the students of senior high school before. Although English is not the new thing for Senior high school students, in fact they still have many difficulties in studying English. In mastering a language, we have to pay attention to the important elements of the language. One of them is language skills including listening, speaking, reading, and writing. These four skills are really important. It can be concluded that in mastering English as a second language, we need these four skills in order to communicate by using this language. Based on the 2006 English standard competence, the purpose of English in literacy education is developing discourse competence. By improving four language skills (listening speaking, reading, and writing), students will be able to develop their discourse competence (Depdiknas, 2006). From the explanation above, writing is considered as one of language skills that has important role to help students develop their productive skill in English. Writing is a means of recording something, information, knowledge and history and express them in the form of written text. Writing is a personal act which writer draws on background knowledge and complex mental process in developing new insights (O’ Malley, 1996:136). Writing is categorized as a productive skill because there is a process of creating something (Abbott et al, 1981: 143). From the explanation above we know that from this skill we get the product in the form of sentence, paragraph, and text. Productive skill consists of speaking and writing. Johnson (2001: 290), stated that writing and speaking are different. Everyone learns to speak but not everyone learns how to write. Writing is more organized and the reader cannot rely on repetition to clarify. Writing has an important role in human’s activity. It creates ideas, information or something which can not be produced by spoken way. Writing also helps students to use language and to express what he wishes or needs to communicate. Furthermore, through writing ability, a student is guided to be an imaginative, creative and motivated person. In fact, writing is considered as the most difficult skill for students. It is supported by (Kroll, 1990) that writing in a second language is more complex, the act of writing in one’s first language is not the same as the act of writing in one’s second language. The difficulties come from the transformation of native language to foreign language. Bell and Burnabi (in Nunan,1991:6) stated that writing is an extremely complex cognitive activity that requires the writer to demonstrate control of several variables at once. At the sentences level, they include control of contents, format, sentence structure, the vocabulary, pronunciation, spelling, and letter formation. Beyond the sentence, the writer must be able to structure and integrate information into cohesive and coherent paragraphs and texts. From the explanation above, students have to think about many things in order to produce a good writing. They have to decide the ideas, vocabulary, and perhaps they worry about grammar and spelling. Those are problems that are faced by students in writing class. According to (Agustien, 2004) when the teachers teach English, their aim is to enable the students to create English sentence grammatically. It means that students who can arrangge sentence grammatically they will can create text in the english. As we know that there are many types of genres text. Agustien also added that every genre is characterized by orientation, complication and resolution. Therefore, when the teachers teach English, it is very important that they expose the learners to authentic English texts in the sense that the text contains grammatical sentences, acceptable expressions, and at the same time properly structured to serve the communicative purpose. The teachers also develop the learners’ ability to write English texts in the way that is culturally acceptable in English culture. In spoken, there are also conversational moves that are common in English conversations. Those are reasons why the teachers need to address some English genres especially those that are often used in school contexts. Wells (1991) cited in Agustien (2004) explained that in teaching Senior High School students, the literacy target which is used is called informational level. It means that Senior High School graduates are expected to be able to access the accumulated knowledge because they are expected to communicate for academic purposes too. The learners are expected to be able to listen to short lectures, talk about serious matters, read popular and scientific texts, and write for different purposes. The kind of genre they learn should include those they are likely to encounter in their academic lives. According to NAEP (1987), the genre defines the style the writer will use and suggest choices about the language and structure of the composition. The text types (genre) which are taught to the Senior High School students are: recount, narrative, procedure, descriptive, news item, report, analytical exposition, hortatory exposition, spoof, explanation, discussion and review. Those texts are differentiated based on their communicative purposes, generic structures and linguistic features. In writing a purposive text or an essay, students will search their memory and recall their knowledge and experience. The knowledge divided into four types; knowledge of generating idea, knowledge of organizing the content, knowledge of discourse structures, and knowledge for integrating all other types of knowledge (O’Malley, 1996: 136- 137). Those areas of knowledge lead problems to the students especially in generating ideas and constructing the generic structure of a purposive text. According to them, getting started to write is the most difficult task in writing activity. They often do not know how to write and what to write about when faced with a topic and a blank piece of paper. This facts show that student dislike writing. According to (Farrugia, 2008) one major factor that shall be tackled to contribute to good writing skills is planning. When attempting any writing task, some people tend to start directly without planning their thoughts. The repercussions when adopting such a hapzard approach is that some ideas are left out and clarity is not achieved. Sorenson (2010) explained that usually, the pre writing activities help us to find a good topic, narrow topics that are too broad, and look at purpose. Listing, free writing, brainstorming, using graphic organizer or mapping and questioning are kinds of technique that used for pre writing activity (Gatz, 2004). Graphic organizers sometimes are also called as concept-maps, entity relationship charts, or mind maps. As Chan (2004) stated mind mapping as a pre writing technique or strategy goes by a variety of names : “mind-mapping”, ”clustering”, “bubbling”, “clumping” or “webbing”. They refer to the same concept. Here the researcher uses the term mind mapping. Mind mapping will be implemented in teaching writing to the eleventh grade students. Because in the eleventh grade, the students are learned by many kinds of genre. This study will take narrative text to be applied to mind mapping. By using mind mapping, the students will easier to organize and generate their ideas for four english skills, especially writing. There were studies which conducted by (Umi nadifah, 2007) which analysed mind mapping as a technique to teach speaking and (Vibriyanida Musdalifah,2008) which use mind mapping to read report text. Mind mapping not only to help them well organized and generate their ideas, but also to help their brain more concentrate to structure and arrange the ideas into cohesive and coherent paragraph. Another reason why the researcher chooses narrative text is due to its subjective and objective details to tell or retell a story, while mind mapping is a technique of arranging and exploring ideas. By using mind mapping to narrative writing, the students are directed to tell or retell story in details systematically. From all of those reason above, the researcher is interested in conducting a study entitled “The use of mind mapping as a technique to teach writing of narrative text to the eleventh grade”. The purpose of this study to know the implementation of mind mapping in teaching and learning process and analyze students’ work after the application of mind mapping. The subject of this reaserch are the the teacher and eleventh Graders of Senior High School students especially Eleventh science 1. METHODOLOGY The research design that used in this study is descriptive qualitative. The data would be presented and analyzed qualitatively without using any statistical instruments because there was no control and treatment group as it is found in the experimental research. The data also be presented in the form of sentences. Thirsterson (2004:359) stated that the descriptive qualitative study is a research relying on the collection of qualitative data and non numerical data such as words and pictures. It means that collecting the information by using descriptive qualitative study were observing, recognizing and understanding what was happened in the classroom. Moreover, Huda (1999) explained that qualitative research is frequently associated with the technique of analyzing data and writing research report. Thus, this research was qualitative because this study focused on describing the implementation of the technique and analyzing the students’ writing composition. The researcher acted as an observer during the teaching-learning process. She only observed, described, and then reported, everything she heared and saw during the class. She evaluated the teaching-learning process and took students’ writing work when the test has held. The subject of the study were the teacher who involve in the teaching and learning process and the eleventh grader students of MAN 2 Gresik. which consist of four science classes and four social. The data of this study is in form of information through observation checklist. Observation checklist described the implementation of mind mapping as a technique in teaching writing narratve texts. Then, the source of data is teacher and students’ activities which happened during the teaching and learning process in the classroom which reported by the researcher using observation checklist. The data of this study also is in form of students’ writing work. They was collected to know the students’ writing ability after they taught using Mind mapping. And The source of the data is the students’ narrative text writing work which the teacher had given in the classroom to the students in the third meeting. Then, the resarcher will analyze the composition of students’ narrative writing work which consist of content, organization, vocabulary, language use and mechanic using ESL Jacob Composition Profile. The instruments which were used in doing this study were observation checklist and students’ work. Observation Checklist is used to describe the implementation of the media and what kind of activities which happened during the teaching learning process in the classroom. In this case, to support the data from the observation, the researcher also used observation checklist as a guidance to know all aspect in the use of mind mapping in teaching narrative text. The students’ work was used by the researcher to conduct this study was the work that given to the students to write a narrative text after the implementation of mind mapping. It was considered as an essential instrument because by giving work to the students, the researcher would know the students narrative writing ability and how mind mapping motivate the students to produce a good narrative text. To collect the data in qualitative research, there are some commonly methods which are used. Wiersman (1991) explained the methods which are used to collect the data in qualitative research are interview, observation, and document collection. In this study, the researcher got the data from the observation by using observation checklist and collected students’ work. After the researcher collected all the data through observation and students’ work then the writer analyzed these data in descriptive way. The way to analyze the data, the data will be collected from the observation checklist which will be described and explained based on the data noted in indicator column with “yes/no” answer. Then, the researcher will analyze the data of the students’ composition from the students’ work. The writer will use Holly Jacobs’ Composition Profile (1981: 91) to analyze the students’ writing work. According to Holly Jacobs’ Composition Profile, there are five aspects which will be analyzed by the researcher to answer the research questions of the study. They are content, organization, vocabulary, language use, and mechanic. The last, All of the data will be combined to make a conclusion and suggestion. The data which come from classroom observation will be analyzed by using descriptive analysis. Then, the researcher will analyze the students’ writing work based on the rubric of ESL composition profile scoring by Jacob (1981). Finally, the researcher will describe the data by classifying them into parts based on the research questions. FINDINGS AND DISCUSSIONS Based on the findings, the implementation of mind mapping was done in three meetings by the teacher. The use of mind mapping technique is as a help to organize the students’ ideas before doing the writing process. The teacher explained how to use mind mapping before the activity. The students using it in group and individually before their writing process. The teacher had reminded the students the generic structures and language feature of narrative text but seemed some of the students forgot it. Then, he tried to explain it again During the teaching and learning process, the teacher used mind mapping as a technique to teach narrative text. The technique was given clear enough for students. In the first meeting, the teacher introduced mindmapping technique to the students. In the second and third meeting, the teacher asked students to compose narrative text using mind mapping in pre writing activity. There were three topics that were given by the teacher. They were Sangkuriang, Snow White and The 7 Dwarfs and Cinderella. In the process of writing, the teacher did not apply all the process, they are pre-writing, drafting, revising and editing. He just focused in pre writing which the implementation use mind mapping technique, Although all the process of writing were not applied, the students can compose narrative text well. Before the teacher asked students to compose narrative text, he asked them to complete mind mapping on the board which was given by the teacher, they were very active. Most of them very enthusiastic to participate complete it. It means the students understand how to use and apply mind mapping. Then, when they asked to compose narrative, they can compose well. It could be seen that by using mind mapping, it can help students to organize and generate their ideas and make them compose narrative well. This is in line with Davis (2003). He stated that mind mapping can be implemented during class to help students, individually or in groups, explore a concept or issue. Then, after the researcher analyzed the students’ work. Most of students can organize and generate their ideas, so they can compose an narrative text well. But, although they could organize and generate their ideas into a narrative text, some of them still had some problems in writing activities. The researcher found the problems related the use of grammar, they had difficulties in constructing sentences to make their writing understandable. The grammar mistakes were in using simple past tense, articles, preposition and pronoun. Beside the grammar mistakes, the teacher also found the problem in choosing and using the words. Some of the students still confused to use appropriate words, so they used inappropriate words that sometimes made the reader difficult to understand the content of the story and there was content that had lack information. Some of them also could not developed well the conflict of the story, some of them also made errors of spelling and capitalization in their writing. However, after the teacher analysed the students’ writing composition, most of students are good criteria in term of content (tells the idea that the writer want to share), organization (deals with the generic structure of the text), vocabulary (describes the students’ knowledge in vocabulary mastery), language use (describes tenses,number, word order or function, articles and prepositions which are in supporting good writing) and mechanics (describes on spelling punctuation and capitalization of writing). It can be said that the mind mapping technique was an effective technique to teach writing narrative. CONCLUSIONS AND SUGGESTIONS Conclusion In conclusion, there were two things that were focused in this study. They were implementation of mind mapping to write a narrative text and the students’ writing ability after being taught by using mind mapping. The implementation of mind mapping of narrative text has several steps; explanation of the technique, grouping and individual works. In each step, the students’ are taught how to use mind mapping in pre-activity to help them organizing their ideas. After making mind mapping, there were students’ works. The process of writing was not apllied completely by the teacher. He just focused in pre-writing activity. During the teaching-learning process, the students were very enthusiastic in making mind mapping. They also very active when the teacher asked them to complete the mind mapping on the board. It could be seen from their direct responses during the teaching-learning process. After analyzed the students’ work, it is known that student’s writing ability is good. Most of students are good in term of content, organization, vocabulary, language use and mechanics. It can be said that the mind mapping technique was an effective technique to teach writing narrative. It can help the students in organizing and generating their ideas in writing. So, they can compose a narrative text well Suggestions Here the researcher would like to propose some suggestions. In the process of teaching English, the teacher should be more creative and selective in choosing the technique which can help them to develop their English skills, especially writing. Mind mapping is one of the the technique. It is implemented in the pre writing activity to help the students to organize and explore their ideas also when they are lacking the ideas. On the other words, it can be said that the teacher should make variations and choose the appropriate and effective technique to teach English, such as by using Mind Mapping. By using this technique, it should encourage the students to be more active and creative and reflect students’ interest, so that they can understand the lesson and get pleasure. Beside that, the teacher should understand the students’s characteristic in order to make the situations of the teaching learning process more enjoyable and make them easier to understand. The teacher should asked the students to practice more using this technique in writing. It can develop their writing skill. For the further reading, the reasearcher believes that there are still many technique that can be used to teach writing narrative text which can make the students more understand the subject. Mind mapping technique is just one of the techniques that can be used to help the students to develop and explore their writing. However it also can be used to teach other skills, such as: speaking and reading. REFERENCES Abbot, et.al. 1981. The Teaching of English as an International Language; A Practical Guide. Great Britain: William Collins Sons and Co.Ltd. Buzan, Tony. (2001). Mind Map untuk meningkatkan kreativitas. Jakarta. PT Gramedia Pustaka Utama. Buzan, Tony. (2006). How to mind map. Jakarta: PT.Gramedia Pustaka Utama Departemen Pendidikan Nasional. 2006. Standart isi dan Standart Kompetensi Lulusan: Mata Pelajaran Bahasa Inggris. Jakarta: Depdiknas. Gebhard, Jerry Greer. 1996. Teaching English as a Foreign or Second Language. USA: The University of Michigan Press. Harmer, Jeremy. 1992. The Practice of English Language Teaching. England: Pearson Education Limited. Harmer, Jeremy. 2002. The Practice of English Language Teaching. New York: Longman Johnshon, Keith. 2001. An Introduction to Foreign Language Learning and Teaching. English: Pearson Education Limited. Kroll, Barbara. 1990. Consideration for Teaching an ESL/EFL Writing Course; Teaching English as A Second or Foreign Language. USA. Heinle and Heinle. Lado, Robert. 1977. Language Testing: The Construction and Use of Foreign Language Test. London: Longman Group, LTD. Langan, John. 2005. College Writing Skills, 6th Ed. New York: The McGraw-Hill,Inc. Lewin, L. 2003. Paving the way in reading and writing: Strategy to Support Struggling Students in Grade 6-12. San Frasisco. United of America Nunan, David.1991. Language Teaching Methodology: A Textbook for Teachers. Great Britain: Prentice Hall International Ltd. O’Malley, J. Michael. 1996. Authentic Assessment for English Language Learners. USA: Addison- Wesley Publishing Company. Richards, J.C and W.A Renandya. 2002. Methodology in Language Teaching: An Anthology of Current Practice. Cambridge: Cambridge University Press.